Pengaruh Sistem Informasi Manajemen Terhadap Efektivitas Kerja di Unit Farmasi Rumah Sakit Islam Ibnu Sina Bukittinggi Tahun 2022 - Dessy Angraini; Ikke Sabrina Putri; Zulfa, Zulfa (Yayasan Literasi Sains Indonesia, 2023)
A good management information system has an influence on the effectiveness of employees' work, including in hospitals. In the pharmacy unit of the Bukittinggi Islamic Hospital, there are several shortcomings in the management information system, such as the input of new drugs that are not directly connected to the management information system at the hospital which causes disruption of waiting times for services at the hospital. The purpose of this study was to determine the effect of management information systems on work effectiveness in the pharmacy unit of the Islamic Hospital Ibnu Sina Bukittinggi. This study uses a cross sectional research method. The study population was all employees in the pharmacy unit of the Islamic Hospital Ibnu Sina Bukittinggi with a sample of 31 people. The sampling technique is total sampling. Data analysis technique is univariate and using structural equation path (smartPLS). The results showed that the t-table value was 1.96 with t-count 0.256, this indicates that t-count t-table means that there is no significant effect of management information systems on work effectiveness in the pharmacy unit of Ibnu Sina Islamic Hospital, Bukittinggi. Based on the r-square, the management information system is only able to affect the work effectiveness of employees by 64.1%, while 35.9% work effectiveness is influenced by other variables.